AB0550 Etiologic Profile of Interstitial Lung Disease in Internal Medecine. (10th June 2014) - Toujani, S.; Ajili, F.; Ben Abdelhafidh, N.; Boussetta, N.; Metoui, L.; Gharsallah, I.; Louzir, B.; Othmani, S.
Abstract : Background: Interstitial lung disease (ILD) is a heterogeneous group of disorders that are classified together because of similar clinical and radiographic manifestations. However, prognosis and therapeutic response are influenced by the presence of an underlying cause. Objectives: The aim is to study the etiologic profile of ILD in internal medicine. Methods: A retrospective analysis of patients with ILD hospitalized in internal medicine department of military hospital from 2000 to 2013. Results: We evaluated 44 patients (30 women, 14 men) with a mean age of 57 years. Among them, 32% were smokers. The most common symptom was progressive dyspnea occurring in 83% of cases. All the patients had abnormal chest radiographs, mainly confluent reticular infiltrates or diffuse reticulonodular shadowing. Pulmonary function tests were restrictive in pattern in 54% of the subjects. The most frequent disease was connective tissue disorders (CTD) - associated ILD (64% of all cases): Sjogren's syndrome (20%), systemic sclerosis (16%), systemic lupus erythematosus (11%), rheumatoid arthritis (9%), antisynthetase syndrome (5%) and dermatomyositis in one case. The diagnostic of both CTD and ILD was made at the same time in 57% of cases. ILD induced by drugs was observed in 16% followed by sarcoidosis in 11% of cases. Idiopathic pulmonary fibrosis was observed in 3 cases and Churg–Strauss syndrome in one case. Corticosteroid therapy was prescribed in 68% of variable dosage depending on the cause and severity of lung disease. Immunosuppressive treatment with cyclophosphamide was indicated in only 4 cases. The response to therapy was favorable in 48% of cases and not satisfactory in 25% of the cases. Conclusions: Collagen and vascular diseases are more common than previously appreciated. A multi-disciplinary evaluation of patients with DPLD can enhance diagnosis, improve prognosis and quality of care. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2378